2012
DOI: 10.1021/ja3014133
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent CO2 Sorption Hysteresis in a One-Dimensional Microporous Octahedral Molecular Sieve

Abstract: The development of sorbents for next-generation CO(2) mitigation technologies will require better understanding of CO(2)/sorbent interactions. Among the sorbents under consideration are shape-selective microporous molecular sieves with hierarchical pore morphologies of reduced dimensionality. We have characterized the non-equilibrium CO(2) sorption of OMS-2, a well-known one-dimensional microporous octahedral molecular sieve with manganese oxide framework. Remarkably, we find that the degree of CO(2) sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 46 publications
5
57
0
Order By: Relevance
“…Such a value can be easily overcome, and is much smaller than both the activation energy barrier for CO2 to bypass the Na + cation as well as the diffusion energy barrier for the K + cation. Research on porous materials exhibited that the cation is movable in the porous tunnels [9,26,40,41]. Our calculations indicate that Scenario III is more energetically favorable, where CO2 pushes the Na + cation to further diffuse along the OMS-2 tunnel.…”
Section: Co2 Sorptionmentioning
confidence: 79%
See 4 more Smart Citations
“…Such a value can be easily overcome, and is much smaller than both the activation energy barrier for CO2 to bypass the Na + cation as well as the diffusion energy barrier for the K + cation. Research on porous materials exhibited that the cation is movable in the porous tunnels [9,26,40,41]. Our calculations indicate that Scenario III is more energetically favorable, where CO2 pushes the Na + cation to further diffuse along the OMS-2 tunnel.…”
Section: Co2 Sorptionmentioning
confidence: 79%
“…It is worth noting that during synthesis of these compounds, H2O molecules can be found to coordinate with the cation and hinder CO2 adsorption uptake [26,34]. However, in a previous experimental study of K-doped OMS-2, it has been shown that upon heating to 150°C, the H2O can be removed without affecting the K + dopant [34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations